Pendidikan di Sekolah Taman Siswa (1922) dan Relevansinya dengan Empat Pokok Kebijakan Merdeka Belajar (2019) - Aprilia Nur Rahmawati; Anggar Kaswati; Siska Nurazizah Lestari (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This study aims to determine: 1) the background to the establishment of the Taman Siswa School; 2) the educational concept of Taman Siswa School; 3) the relevance of the Taman Siswa School’s educational concept with Merdeka Belajar Policy. The method used is a historical research method with the stages of selecting topics, heuristics, verification, interpretations and historiography. The result of the study revealed that 1) Taman Siswa School was founded on July 3, 1922 in Yogyakarta by Ki Hajar Dewantara as a form of action against the state of education during the colonial government; 2) Education at Taman Siswa School is very concerned about achieving the ideal development of student by guiding them to become human beings who are independent both physically and mentally in accordance with the natural forces within each of them; 3) There is relevance between the concept of education at Taman Siswa School with Merdeka Belajar Policy is about the basis of the independence in carrying out education, the role of the teacher, and coorperation in realizing education (between schools, families and communities).